Efeito do ácido acetilsalicílico na ativação plaquetária e perfil oxidativo em pacientes com Diabetes Mellitus tipo 2 - Rita Carolina Figueiredo Duarte (2012)
Type 2 diabetes mellitus (DM2) is a metabolic disorder associated with cardiovascular complications, hyperactivation of platelets and consequent increased formation of platelet microparticles (MP). Oxidative stress is also related to macrovascular and microvascular complications of the diabetes, and the activated platelets produce reactive oxygen species (ROS) which are prothrombotic and moreover, ROS are related to the propagation of platelet activation. Acetylsalicylic acid (ASA) is an antiplatelet agent used in the prevention of atherothrombotic events by blocking the formation of thromboxane A2 via inhibition of platelet cyclooxygenase-1. The effect of ASA can be determined by the levels of 2,3-dinor-thromboxane B2 (2,3-dinor-TXB2), and 11-dehydro-thromboxane B2 (11-dhTXB2). In order to evaluate the response to ASA by means platelet activation and oxidative profile, we collected samples of blood and urine of 81 patients with DM2 in two distinct moments, the first immediately prior to initiation of treatment with ASA and the second, at the fifteenth day of treatment with 100 mg of this medication daily. These samples were analyzed to determine the urinary 11-dhTXB2 and plasma levels of 2.3 dinorTXB2 and MPs. Furthermore, were measured levels of thiobarbituric acid reactive species (TBARS) and 3 - (4,5-dimethylthiazol-2yl) -2,5-diphenyltetrazolium bromide (MTT) for evaluation of lipid peroxidation and antioxidant status of serum, respectively. It was observed a significant decrease in the levels of 2.3 dinorTXB2 (p <0.001) and 11-dhTXB2 (p = 0.00), however most of the patients showed a reduction in levels of these markers, at the maximum, 90%. On the other side, no significant difference was found between the levels of MP, TBARS and MTT before and after use of AAS. These results analysed together indicate that ASA did not change the MP and oxidative profiles and that patients did not show an equal and satisfactory response to this drug. This finding is consistent with previous reports in the literature that patients with DM2 do not benefit in an equal way from the use of aspirin for primary prevention of atherothrombotic events.